UPAYA MENINGKATKAN ADVERSITY QUOTIENT MELALUI PELAKSANAAN BIMBINGAN KLASIKAL (Penelitian Pada Mahasiswa Semester III Program Studi Bimbingan Dan Konseling FKIP UNISRI TAHUN 2014/2015) - Putro, Eko Adi (UNIVERSITAS SLAMET RIYADI, 2015)
The background of the research is the phenomenon of people facing troubles and challengein life which is responded with hopelessness. They are considered to have low adversity quotient.These symptoms were found during counseling among students of Guidence and Counceling ofSlamet Riyadi University 2015. This phenomenon was recorded by their scores which were onlyE and D. It was found that the everage number is two for each class group. The improvement ofadversity quotient was conducted through basic service counceling program namely classicalprogram. This program drives councelors to make a direct contact with the students in theirclassrooms through discussion and ideas sharing. It is hoped that the studentsâ€™ adversityquotients improve.The topic given during the classical counceling were those related to the goal of thecounceling in the adversity quotient research. They are destructive thinking, adversity quotient,education film entitled â€œSuccesful diffablesâ€, â€œINSIGHT 12 SPSSâ€The research applied class room action research with two cycles. The steps cover 1)planning, 2) action, 3) observation, 4) reflection. This research also applied adversity responseprofile for data collecting.The result shows that the studentsâ€™ adversity quotient improved after cycle 1. It is indicatedby the decrease of the number for those with the lowest score 31,25% became only 6,25%, andfor those with medium score 9,375 increased into 31,25%, and those with highest score 9,375%.In cycle 2 the number increased significantly signed by the disapearance of the lowest and lowcgroup.Based on the research, it is suggested; 1) to increase the adversity quotient for students,classical counceling with speech and film is suggested, 2) to choose interesting film to be usedduring the counceling to increase the adversity quotient.Keywords: adversity quotient, classical counceling